Whole‐body MRI for metastatic cancer detection using T2‐weighted imaging with fat and fluid suppression. Issue 4 (14th February 2018) - Wang, Xinzeng; Pirasteh, Ali; Brugarolas, James; Rofsky, Neil M.; Lenkinski, Robert E.; Pedrosa, Ivan; Madhuranthakam, Ananth J.
Abstract : Purpose: To develop a whole‐body MRI technique at 3T with improved lesion conspicuity for metastatic cancer detection using fast, high‐resolution and high SNR T2 ‐weighted (T2 W) imaging with simultaneous fat and fluid suppression. Theory and Methods: The proposed dual‐echo T2 ‐weighted acquisition for enhanced conspicuity of tumors (DETECT) acquires 4 images, in‐phase (IP) and out‐of‐phase (OP) at a short and a long TE using single‐shot turbo spin echo. The IP/OP images at the short and long TEs are reconstructed using the standard Dixon and shared‐field‐map Dixon reconstruction respectively, for robust fat–water separation. An adaptive complex subtraction between the 2 TE water‐only images achieves fluid attenuation. DETECT imaging was optimized and evaluated in whole‐body imaging of 5 healthy volunteers, and compared against diffusion‐weighted imaging with background suppression (DWIBS) in 5 patients with known metastatic renal cell carcinoma. Results: Robust fat–water separation and fluid attenuation were achieved using the shared‐field‐map Dixon reconstruction and adaptive complex subtraction, respectively. DETECT imaging technique generated co‐registered T2 W images with and without fat suppression, heavily T2 W, and fat and fluid suppressed T2 W whole‐body images in <7 min. Compared to DWIBS acquired in 17 min, the DETECT imaging achieved better detection and localization of lesions in patients with metastatic cancer. Conclusion: DETECT imaging technique generates T2 W images with high resolution, high SNR, minimal geometric distortions, and provides good lesion conspicuity with robust fat and fluid suppression in <7 min for whole‐body imaging, demonstrating efficient and reliable metastatic cancer detection at 3T.